A new protection scheme for loss of excitation detection in presence of FACTS devices. (July 2019) - Moravej, Zahra; Rasooli, Hedieh; Pazoki, Mohammad
Highlights: The impact of FACTS on LOE protection scheme is investigated. Useful features are extracted based on simulation results to detect LOE condition. Two classifiers are compared and the most appropriate one is selected. The proposed scheme improves the LOE protection function in presence of FACTS. The proposed scheme discriminates LOE from SPS to prevent mal-operation of relay. Abstract: Loss of excitation (LOE) in synchronous generators can cause damage on both generators and power system. In the conventional method, LOE is detected by using mho negative offset. In this case, the speed of detection is low and also in some condition, a stable power swing can be detected by mistake. The mal-operation of conventional LOE relay can cause a blackout. Moreover, the presence of flexible alternating current transmission system (FACTS) devices change the impedance that measured by LOE relay, and hence it affects the performance of a LOE relay. In this paper, the validity of electrical and mechanical quantities is discussed. Therefore, some suitable electrical and mechanical features among the quantities are extracted. Then the classifier is employed and to evaluate the performance of the proposed scheme, some case of LOE, partial LOE (PLOE), and stable power swing (SPS) are simulated. The obtained results show that the proposed scheme is robust and secure to discriminate LOE from SPS. In addition, the proposed scheme is fast and adequate to detect LOE in the presence of FACTS devices due to delay time raised by compensation devices.